PERBANDINGAN TINGKAT KESEHATAN BANK UMUM KONVENSIONAL DAN BANK UMUM SYARIAH MENGGUNAKAN METODE RGEC (RISK PROFILE, GOOD CORPORATE GOVERNANCE, EARNINGS, DAN CAPITAL) - Zettyra R. D, Zara; Mutia, Evi (Accounting Departement Economics and Business Faculty Syiah Kuala University, 2019)
The purpose of this study was to see a comparison of the health levels of conventional commercial banks and Islamic commercial banks using the RGEC method in the 2014-2017 period. The sample of this study were 30 conventional commercial banks and 11 sharia commercial banks. The assessment used uses the RGEC method (Risk Profile, Good Corporate Governance, Earnings, Capital) Risk Profile seen through the NPL and NPF indicators for conventional commercial banks while Islamic banks use LDR and FDR. Corporate governance is measured through Self Assessment. Earnings are measured through ROA and NIM indicators. Capital is measured based on the CAR indicator. Testing the hypothesis in this study using the Independent T-Test and Mann-Wnithey Test samples. The results of this study indicate that there is a difference between conventional commercial banks and Islamic commercial banks seen from the ratio of NPL, LDR, and ROA. While the ratio of GCG, NIM, and CAR does not have a significant difference between conventional commercial banks and Islamic commercial banks.